Effort to increase rubber farmers’ income when rubber low prices - Iman Satra Nugraha; Aprizal Alamsyah; Sahuri Sahuri (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
Rubber is a plantation crop that has high economic value and the largest foreign exchange producer 10. Rubber producers in Indonesia consist of the islands of Sumatra and Kalimantan. Indonesia is one of the largest rubber producers after Thailand with the number of people involved in rubber farming reaching 2.2 million households. The recent decline in rubber prices has affected the decline in rubber farmers' income. So a strategy is needed to increase the income of rubber farmers. This paper provides an overview of the strategies that rubber farmers need to increase their income. The strategy that was carried out was an increase in the adoption of superior clones at the farmer level, optimization of rubber plantations by modifying the distance of rubber plants to be wider so that they could be used to plant intercrops during the rubber crop cycle and farmers using rubber marketing through UPPB (row rubber material processing and marketing unit)because it could increase the share price received by farmers so farmers get high prices.